Glomerular Filtration Rate in Prediabetic Subjects in Kendari City - Orno, Theosobia Grace; Atmaja, Ratih Feraritra Danu; Supiati, Supiati; Hasan, Aswiro (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Prediabetes is a condition of impaired blood glucose metabolism. However, it does not yet meet the criteria for diabetes mellitus, characterized by impaired fasting blood glucose (FBG) levels and the Oral Glucose Tolerance Test (OGTT). Chronic glucose intolerance can increase the workload of the kidney glomerulus in the filtration process and the tubules in the reabsorption process. The research aims to assess the Glomerular Filtration Rate (GFR) in prediabetic subjects in Kendari. This type of analytical observational research with a case-control design. The total sample was 90 samples consisting of 45 non-diabetic samples as the control group and 45 prediabetic samples as the case group. Characteristic data is presented as a frequency distribution and test data for differences between the control group and cases using an independent t-test with statistical test results said to be significant if the p-value is less than 0.05. The research results showed that the frequency distribution of subjects in the control group and cases based on gender was dominated by women, with the most extensive age range being 36-55 years. The FBG variable in the control group had a mean of 94±5.31 mg/dL, and in the case group, 110±8.09 mg/dL. The OGTT value in the control group was 118±12.78 mg/dL, and the case group was 139±23.90 mg/dL. The results of the calculation of the GFR showed a mean of 98.63±14.28 mL/min/1.73 m2 in the control group and 50.10±16.34 mL/min/1.73 m2 in the case group, different significant (p equal 0.000). There was a significant difference between GFR in the control group and the prediabetes case group. The results of the GFR assessment in the prediabetes group showed a mild decrease in renal function.